2003
DOI: 10.1007/s00418-003-0585-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression of stabilin-2, a novel fasciclin-like hyaluronan receptor protein, in murine sinusoidal endothelia, avascular tissues, and at solid/liquid interfaces

Abstract: Stabilin-2, the hepatic hyaluronan receptor, has recently been cloned by us. Together with stabilin-1, stabilin-2 constitutes a novel family of fasciclin-like hyaluronan receptor homologues. Here, we analyzed expression of stabilin-2 (mStab-2) in a broad array of C57BL/6 mouse organs and tissues. While northern blot analysis showed positive expression of mStab-2 mRNA confined to liver and spleen, immunohistochemistry demonstrated mStab-2 protein expression in the endothelial sinuses of liver, lymph nodes, sple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
144
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(151 citation statements)
references
References 55 publications
7
144
0
Order By: Relevance
“…Unlike other molecules, which are expressed ubiquitously, stabilin-2 is expressed in specific cell types, including sinusoidal endothelial cells of the spleen, lymph node, and liver, 21 as well as macrophages. It has been reported in previous studies that stabilin-2 is only barely detectable in monocytes/macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike other molecules, which are expressed ubiquitously, stabilin-2 is expressed in specific cell types, including sinusoidal endothelial cells of the spleen, lymph node, and liver, 21 as well as macrophages. It has been reported in previous studies that stabilin-2 is only barely detectable in monocytes/macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a few studies have demonstrated that stabilin-1, the closest homologue of stabilin-2, is expressed in macrophages. 19,21 Stabilin-1 and stabilin-2 have similar domain structures and expression patterns, and also operate as scavenger receptors. 17,19,20 In this point, stabilin-1 may be also involved in the clearance of apoptotic cells in macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another candidate is the HA receptor for endocytosis. It can be expressed on the cell surface, but it predominately localizes within sinusodial endothelia and its expression by lymphocytes has not been reported (35,36). Interestingly, antibody blockage of HA binding to HA receptor for endocytosis impairs tumor cell metastasis, a process likened to active lymphocyte extravasation (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Orthologues of this receptor are present in other mammals, including cow, pig, guinea pig, rat, mouse, and human (27). Human and rat HARE are primarily found in the sinusoidal endothelial cells of the lymph nodes, liver, and spleen (28 -31).…”
mentioning
confidence: 99%